THE STUDY OF ENGLISH WORD FORMATION IN AMERICAN COMIC STRIPS: Superman Vs the Amazing Spider-Man and Batman Vs the Incredible Hulk - RAHMIATI, Tri (2012)
This paper entitled The Study of English Word Formation in American Comic Strips: Superman Vs the Amazing Spider-Man and Batman Vs the Incredible Hulk is aimed at finding out the types of word formation processes appear in the two comics and at finding out the context of situation that leads to the usage of the word-formation processes. This study employed qualitative research design. The sources of this study are two American comic books published by DC comic and Marvel comic. The data were collected through intensively reading and identifying the types of the word formation processes by using their characteristics that were based on word-formation theory by O'Grady (1997) and Carstairs-McCarthy (2002). This study reveals that besides acronym, onomatopoeia, clipping, blending and derivation, the most frequently used word-formation process is compounding. This result appears due to the fact that the character's names in the two comics were a sample of compounding process. Furthermore, the study also shows that the context of situation that leads to the usage of the word-formation process were varied from introduction, mocking, venting anger, delivering news, and complaining. In addition the study also finds out that there are different contexts that lead to the usage of the same word-formation processes.